Co-Financing Hollywood Film Productions with Outside Investors An Economic Analysis of Principal Agent Relationships in the U.S. Motion Picture Industry - Hofmann, Kay H. (Markt- und Unternehmensentwicklung / Markets and Organisations, 2013)
Co-financing arrangements in which investors from outside the motion picture industry become co-owners of the completed films are a common phenomenon in Hollywood. Kay H. Hofmann analyzes the conflicts of interest and the organizational problems that may arise between the experienced major studios and investors with comparably low industry expertise. Guided by principal agent theory, the empirical analysis provides evidence for adverse selection and moral hazard. Based on his findings, the author develops solutions that are not only relevant for investors but also for film producers who rely on the long-term availability of external funds.